Analysis of the mechanical performance and damage mechanism for 3D printed concrete based on pore structure. (3rd January 2022) - Liu, Chao; Zhang, Rongfei; Liu, Huawei; He, Chunhui; Wang, Youqiang; Wu, Yiwen; Liu, Shuhua; Song, Lin; Zuo, Fan
Highlights: Pore structure was studied to analyse the defects in 3DPC at a meso level. Relationship between pore structure and compressive strength of 3DPC was analysed. Ultimate compressive strength of 3DPC and its damage mechanism were analysed. Three-dimensional stress field distribution at the 3DPC interface was predicted. Abstract: 3D printed concrete (3DPC) technology is one of the fastest-growing technologies in the construction industry. In this study, the pore structure of 3DPC and its parameters were investigated. The variation patterns of compressive strength, splitting tensile strength, and flexural strength of 3DPC were studied with the increase of curing time in different loading directions. Characterisation of the meso -destructive mechanism and ultimate strength of 3DPC by X-ray computed tomography (X-CT) and the digital image correlation (DIC) techniques is conducted. The results showed that the internal pore structure of 3DPC was different from that of cast concrete, showing irregular shapes and the pores were prone to stress concentration, resulting in the mechanical strength of 3DPC being generally lower than that of cast specimens. Moreover, the mechanical strength of 3DPC showed significant anisotropy. 3DPC showed variability in the relationship between its pore structure and strength when compressed in the X-, Y- and Z-directions. The ultimate compressive strength of 3DPC and its damage mechanism were analysed based on the parallel pore connection model. The three-dimensional stress field distribution at the 3DPC interface was predicted when the cracks extend along the direction parallel or perpendicular to the interface.